Chromatographic isolation of the hemagglutinin polypeptides from influenza virus vaccine and determination of their amino-terminal sequences. - Bucher, D J (1976)
The influenza virus hemagglutinin polypeptides, HA1 and HA2, have been purified by gel filtration in the presence of sodium dodecyl sulfate from a vaccine preparation of the recombinant strain Heq1N2. Use of this technique for purification of the hemagglutinin polypeptides eliminated the need for proteolytic agents for removal of the hemagglutinin from the virus particles and 100-300 mg of virus yielded 10-30 mg of viral protein per chromatographic cycle. Because proteolysis is not required to remove the spikes from the viral envelope, the envelope-embedded HA2 polypeptide was purified in its entirety for structural analysis. Amino-terminal sequence analysis of the smaller polypeptide, HA2, revealed a cyclic repetition of glycyl residues through the first 24 residues at every third to fourth position. The sequence through the first 10 residues was identical to that presented by Skehel and Waterfield for other type A influenza viruses [(1975) Proc. Nat. Acad. Sci. USA 72, 93-97]. The HA1 (Heq/) polypeptide, on the other hand, had different amino acids at three or four out of the first 10 residues of the amino-terminal sequence when compared to HA1 from H0, H1, or H2 subtypes (Skehel and Waterfield). The present study has demonstrated the feasibility of the use of vaccine virus as a source of large quantities of viral protein for determination of primary structure.